Peri-infarct blood-brain barrier dysfunction facilitates induction of spreading depolarization associated with epileptiform discharges - Lapilover, E. G.; Lippmann, Kristina; Salar, Seda; Maslarova, A.; Dreier, J. P.; Heinemann, U.; Friedman, A. (Neurobiology of Disease, 2012)
Recent studies showed that spreading depolarizations (SDs) occurs abundantly in patients following ischemic stroke and experimental evidence suggests that SDs recruit tissue at risk into necrosis. We hypothesized that BBB opening with consequent alterations of the extracellular electrolyte composition and extravasation of albumin facilitates generation of SDs since albumin mediates an astrocyte transcriptional response with consequent disturbance of potassium and glutamate homeostasis. Here we show extravasation of Evans blue-albumin complex into the hippocampus following cortical photothrombotic stroke in the neighboring neocortex. Using extracellular field potential recordings and exposure to serum electrolytes we observed spontaneous SDs in 80% of hippocampal slices obtained from rats 24h after cortical photothrombosis. Hippocampal exposure to albumin for 24h through intraventricular application together with serum electrolytes lowered the threshold for the induction of SDs in most slices irrespective of the pathway of stimulation. Exposing acute slices from naive animals to albumin led also to a reduced SD threshold. In albumin-exposed slices the onset of SDs was usually associated with larger stimulus-induced accumulation of extracellular potassium, and preceded by epileptiform activity, which was also observed during the recovery phase of SDs. Application of ifenprodil (3μM), an NMDA-receptor type 2 B antagonist, blocked stimulus dependent epileptiform discharges and generation of SDs in slices from animals treated with albumin in-vivo. We suggest that BBB opening facilitates the induction of peri-infarct SDs through impaired homeostasis of K+. © 2012 Elsevier Inc.
Created from Fastlane, Scopus look-up
Keywords: Astrocytes; Blood-brain barrier; Photothrombosis; Potassium homeostasis; Spreading depolarization; Stroke